Biaya Produksi, Volume Penjualan, dan Kualitas Produk Terhadap Pendapatan - Annisa Rahmawati; Ruly Priantilianingtiasari (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine the effect of production costs, sales volume, and product quality on the income of laying hens in Blitar. This research method is quantitative. Utilizing google form as primary data. The population in this study were laying hens in Ponggok District, Blitar Regency. The sample generated using the Slovin formula is 91 respondents. Using the SPSS application version 26 to analyze data. The results showed that partially the production cost variable had no effect and was not significant on income with a significance of 0.453 and tcount of 0.754. Partially, the sales volume variable has a significant and significant effect on income with a significance of 0.000 and tcount of 4.123. Partially, product quality variables have significant and significant effect on income with a significance of 0.000 and tcount of 4.471. Simultaneously the variables of production costs, sales volume and product quality have a significant and significant effect on income with a significance of 0.000 and Fcount 45.929. In conclusion, the production cost variable has no effect on income, but the sales volume and product quality variables have an effect on the income of laying hen breeders in Blitar. Meanwhile, the variables of production costs, sales volume and product quality together affect the income of laying hens in Blitar. Keywords: Production Cost, Product Quality, Revenue, Sales Volume